Malaria in the social context : a study in western India - Lobo, Lancy, S.J. (London ; New York : Routledge, 2010)
Study conducted in Surat district, Gujarat, India.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Malaria -- Social aspects -- India -- Sūrat (District) -- Case studies; Electronic books